2022
DOI: 10.1002/jbio.202200001
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance biosensor based on graphene layer for the detection of waterborne bacteria

Abstract: As a result of the risks that waterborne bacteria bring to the human body, identifying them in drinking water has become a global concern. In this article, a highly sensitive surface plasmon resonance (SPR) biosensor consisting of prism, Ag, graphene, affinity layer and sensing medium is proposed for rapid detection of the waterborne bacteria. Four SPR‐based sensors are first studied with the structures prism/Ag/sensing medium, prism/Ag/affinity layer/sensing medium, prism/Ag/graphene/sensing medium, and prism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…2020 156.33 [44] An SPR sensor employing a thin layer of plasma. 2021 103 [45] An SPR biosensor based on G. 2022 199.87 [32] Detection of fat concentration in milk using SPR biosensor based on Si and Ti 3 C 2 T x . 2022 350 Current work…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020 156.33 [44] An SPR sensor employing a thin layer of plasma. 2021 103 [45] An SPR biosensor based on G. 2022 199.87 [32] Detection of fat concentration in milk using SPR biosensor based on Si and Ti 3 C 2 T x . 2022 350 Current work…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we demonstrated four different commonly used prisms, which are N-FK51A, 2S2G, SF10, and BK7. We found that structures with N-FK51A and BK7 had the highest sensitivity [ 32 ]. It was shown in the same study that sensor sensitivity can be enhanced when using a low refractive index prism.…”
Section: Structure Considerationmentioning
confidence: 99%
“…The principle behavior of SPR-based sensors typically includes fiber-optic SPR [ 258 , 259 ], SPR imaging [ 260 , 261 ], and localized SPR [ 262 , 263 ]. Recently, the four SPR biosensors consisting of prism, Ag, graphene, affinity layer, and sensing medium, were studied to detect bacteria in drinking water [ 264 ]. The as-designed SPR sensor exhibited a high sensitivity of Escherichia coli (223.63°/RIU) and Vibrio cholera (199.87°/RIU).…”
Section: Other Nanomaterial-based Methodologymentioning
confidence: 99%
“…A highly sensitive SPR biosensor consists of the prism, gold coating, graphene, affinity layer, and sensing medium for the detection of waterborne pathogens. The structural parameters of the biosensor were optimized to attain a higher sensitivity of 221.63°/RIU for E. coli and 178.12°/RIU for Vibrio cholera pathogen with an average value of 199.87°/RIU [ 56 ]. An optical sensor based on thin liquid film was designed by combining the SPR, light extinction, and near-critical angle reflection.…”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%